High-pressure autohydrolysis process of wheat straw for cellulose recovery and subsequent use in PBAT composites preparation. (January 2022) - Fiorentini, C.; Bassani, A.; Duserm Garrido, G.; Merino, D.; Perotto, G.; Athanassiou, A.; Peräntie, J.; Halonen, N.; Spigno, G.
Abstract: The effect of autohydrolysis (AH) temperature (165 °C, 195 °C, 225 °C) on the structure, purity, and recovery yield of the cellulose residue isolated after additional alkaline and bleaching steps from wheat straw, was investigated. The processes were quantified for mass yields in the different steps and for antioxidants and sugars release during AH. AH at 195 °C allowed for the highest cellulose residue yield (83.5%) with purity (∼70%) and structure similar to the other residues. FTIR and XRD analyses showed straw cellulose (SC) with a type II polymorphism and crystallinity index increasing with AH temperature. SC obtained at the end of the entire fractionation process (SC-195 °C) starting from AH residue-195 °C was tested as a reinforcing agent in different percentage (0, 2 and 5% by weight) in poly(butylene adipate- co -terephthalate) (PBAT) films. The Young's modulus of the films increased by ∼17% with 5 wt% cellulose, while tensile strength and elongation at break decreased. Graphical abstract: Image 1 Highlights: Investigation of autohydrolysis pretreatment for cellulose recovery from wheat straw Effect of autohydrolysis on cellulose purity and structure Cellulose from autohydrolysis tested as a reinforcing agent for PBAT films Improvement of Young's module of PBAT films with cellulose